The mediating effect of digital economy on international trade -- Evidence from China - Xu Qian (SHS Web of Conferences, 2023)
According to the World Economic Forum, for every 10% increase in a country’s digitalization, the country’s GDP per capita grows by 0.5%~0.62%, and the potential of the digital economy cannot be ignored. Based on the inter-provincial panel data of China from 2010 to 2020, this paper constructs a mediating effects model to analyze the path of the digital economy affecting foreign trade through human capital and industrial upgrading, and then explores the impact of human capital and industrial economy on foreign trade in different geographical conditions from a geographical perspective. It is found that there is a significant mediating effect of human capital and industrial upgrading in the process of digital economy’s influence on foreign trade development, and this effect is regionally heterogeneous, playing a better role in the eastern coastal region than the central and western regions. In order to narrow the regional gap, a balanced layout of educational resources is realized to improve the human capital level in the central and western regions, and a mechanism of industrial synergy development in the central and western regions is established.